A genome-wide regulatory network of INTS12 associated with pulmonary function - Kheirallah, Alexander K. (2017)
Genome-wide association studies of human lung function and Chronic Obstructive Pulmonary Disease have identified a highly significant and reproducible signal on 4q24. It remains unclear which of the two candidate genes within this locus may regulate lung function: GSTCD, a gene with unknown function, and/or INTS12, a member of the Integrator Complex which is currently thought to mediate 3’end processing of small nuclear RNAs. An interrogation of bioinformatic datasets showed that in lung tissue, 4q24 polymorphisms associated with lung function correlate with INTS12 but not neighboring GSTCD expression. In contrast to the previous reports in other species, a minor alteration of small nuclear RNA processing was observed following INTS12 depletion. RNA sequencing analysis of knockdown cells instead revealed dysregulation of a core subset of genes relevant to airway biology and a robust downregulation of protein synthesis pathways. Consistent with this, protein translation was decreased in INTS12 knockdown cells. In addition, chromatin immunoprecipitation and sequencing experiments demonstrated INTS12 binding throughout the genome, which was enriched in transcriptionally active regions. Finally, INTS12 regulome was defined which includes genes belonging to the protein synthesis pathways. INTS12 has functions beyond the canonical snRNA processing and evidence is presented showing that it regulates translation by directly controlling the expression of genes belonging to protein synthesis pathways. This thesis provides a detailed analysis of INTS12 activities on a genome-wide scale and contributes to the understanding of biology behind the genetic association for lung function at the 4q24.